2021
DOI: 10.21873/anticanres.15203
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications of Jejunal and Skin Valve Reconstruction in Free Reconstructive Surgery for Hypopharyngeal Carcinoma

Abstract: Background/Aim: This study evaluated the incidence of perioperative complications in jejunal flap compared with the free tissue flap approach. Patients and Methods: This study included 75 patients who underwent free flap reconstruction for hypopharyngeal carcinoma. The primary outcome was the incidence of pharyngocutaneous fistula, and the secondary outcomes were perioperative complications. Results: Pharyngocutaneous fistula developed in 7% of patients who underwent jejunal flap procedures and 6% of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Furthermore, some studies have demonstrated the postoperative function of cutaneous free tissue flap [ 8 ]. Our previous study on free jejunal and cutaneous free tissue flaps reconstruction in 75 patients with hypopharyngeal cancer showed no significant difference in the incidence of cervical complications between free jejunal and cutaneous free tissue flaps reconstruction ( p = 0.99); however, we demonstrated significantly higher donor site complications in the free jejunal flap group than in the cutaneous free tissue flap group ( p = 0.03) [ 9 ]. Notably, however, few Japanese studies have demonstrated the benefits of cutaneous free tissue flaps.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Furthermore, some studies have demonstrated the postoperative function of cutaneous free tissue flap [ 8 ]. Our previous study on free jejunal and cutaneous free tissue flaps reconstruction in 75 patients with hypopharyngeal cancer showed no significant difference in the incidence of cervical complications between free jejunal and cutaneous free tissue flaps reconstruction ( p = 0.99); however, we demonstrated significantly higher donor site complications in the free jejunal flap group than in the cutaneous free tissue flap group ( p = 0.03) [ 9 ]. Notably, however, few Japanese studies have demonstrated the benefits of cutaneous free tissue flaps.…”
Section: Introductionmentioning
confidence: 63%
“…Cervical complications were classified as fistulas, flap necrosis, lymph fistulas, hemorrhage, and infection. We used the surgical procedure described in detail by Tokaashiki et al [ 9 ]. Skin incision and insetting the flap were performed by head and neck surgeons, whereas free jejunal flap reconstruction was performed by a gastroenterologist.…”
Section: Methodsmentioning
confidence: 99%